STRUCTURAL FEATURES OF UZBEK JUDICIAL TERMS - Minavarov Khusan (Bright Mind Publishing, 2025)
This research explores the structural features of judicial terms in the Uzbek language, focusing on their formation methods and linguistic characteristics. The study analyzes how affixation, compounding, abbreviation, and other word-formation techniques contribute to the development of legal terminology. Particular attention is given to productive affixes such as -chi, -lik, and -lov/-uv, which play a significant role in the creation of professional and procedural terms. The paper also highlights the historical and functional relevance of these terms in the context of Uzbek judicial discourse. Through examining the semantic and morphological aspects of legal vocabulary, the study aims to deepen the understanding of the Uzbek legal lexicon and its structure within the broader framework of theoretical and applied linguistics.
Keywords: legal, court, judicial system, terminology, affixatation.